Non-Coding RNA in Tumor Cells and Tumor-Associated Myeloid Cells—Function and Therapeutic Potential - Binder, Amanda; Bremm, Franziska; Dörrie, Jan; Schaft, Niels (International Journal of Molecular Sciences, 2024)
The RNA world is wide, and besides mRNA, there is a variety of other RNA types, such as non-coding (nc)RNAs, which harbor various intracellular regulatory functions. This review focuses on small interfering (si)RNA and micro (mi)RNA, which form a complex network regulating mRNA translation and, consequently, gene expression. In fact, these RNAs are critically involved in the function and phenotype of all cells in the human body, including malignant cells. In cancer, the two main targets for therapy are dysregulated cancer cells and dysfunctional immune cells. To exploit the potential of mi- or siRNA therapeutics in cancer therapy, a profound understanding of the regulatory mechanisms of RNAs and following targeted intervention is needed to re-program cancer cells and immune cell functions in vivo. The first part focuses on the function of less well-known RNAs, including siRNA and miRNA, and presents RNA-based technologies. In the second part, the therapeutic potential of these technologies in treating cancer is discussed, with particular attention on manipulating tumor-associated immune cells, especially tumor-associated myeloid cells.
CRIS-Team Scopus Importer:2024-07-19
Keywords: cancer therapy; myeloid-derived suppressor cells; non-coding RNA; tumor-associated dendritic cells; tumor-associated macrophages; tumor-micro-environment